Fast mapping in hominids - Dahliane Labertoniere; Vanessa A. D. Wilson; Carla Pascual-Guàrdia; Katrin Skoruppa; Klaus Zuberbühler (Animal Cognition)
Abstract Fast mapping is essential when children acquire language, but whether the required cognition is uniquely human or shared with animals is debated. Although documented in dogs and cats, both species have a history of domestication of social cognition, so that it remains unclear whether fast mapping is naturally present in non-domesticated animals. Here, we used an eye-tracking paradigm to test three species of hominids – gorillas, orangutans and humans – in their ability to rapidly learn to associate novel sounds with objects in their everyday noisy environment. The task was difficult for all participants, but while adult humans showed evidence of fast mapping, we could not detect any sign of learning in the other hominids. These species differences could have trivial causes, such as problems with attention or motivation, but it is also possible that fast mapping requires a preexisting lexicon before becoming an effective learning mechanism, or that it has simply evolved after the shared ancestor of all great apes.